Brainstem morphological changes in Alzheimer's disease. Issue 7 (6th May 2015) - Lee, Ji Han; Ryan, John; Andreescu, Carmen; Aizenstein, Howard; Lim, Hyun Kook
Abstract : As brainstem nuclei are interconnected with several cortical structures and regulate several autonomic, cognitive, and behavioral functions, it might be important to place the brainstem within an important pathologic core in the progression of Alzheimer's disease (AD). Although there have been several postmortem studies reporting neuropathological alterations of the brainstem in AD, there has been no in-vivo structural neuroimaging study of the brainstem in the patients with AD. The aim of this study was to investigate differences in the brainstem volume and shape between patients with AD and elderly normal controls. Fifty AD patients (the Clinical Dementia Rating Scale≥1) and 50 normal controls were recruited, and the brainstem volumes and deformations were compared between the AD and the controls. Patients with AD showed significant total volume [(mean±SD) 21007±1640 mm 3 ] reduction in the brainstem compared with the controls [(mean±SD) 22530±1750 mm 3 ] ( P <0.001). In addition, AD patients showed significant brainstem deformations in the upper posterior brainstem corresponding to the midbrain compared with the healthy individuals (false discovery rate corrected P <0.05). This study is the first to explore brainstem volume change and deformations in AD. These structural changes in the midbrain areas might be at the core of the underlying neurobiological mechanisms of brainstem dysfunction with relevance to their various cognitive and behavioral symptoms such as memory impairment, sleep, and emotional disturbance in AD. However, further longitudinal studies might be needed to confirm these findings.